Do Negative Interest Rates Make Banks Less Safe? - Federico Nucera; Andre Lucas; Julia Schaumburg; Bernd Schwaab (Tinbergen Institute, 2017)
We study the impact of increasingly negative central bank policy rates on banks' propensity to become undercapitalized in a financial crisis (`SRisk'). We find that the risk impact of negative rates depends on banks' business models: Large banks with diversified income streams are perceived as less risky, while smaller and more traditional banks are perceived as more risky. Policy rate cuts below zero trigger different SRisk responses than an equally-sized cut to zero.
Keywords: G20; G21; 330; negative interest rates; bank business model; systemic risk; unconventional monetary policy measures